On corruption in public administration: a study from the professionalization of the public servant - Rodríguez Amaya, Oswaldo (2025)
Corruption within public administration is a persistent phenomenon in most Latin American countries. It is a structural problem with multiple causes that manifests itself at different levels and in different areas of government activity, making it significantly difficult to eradicate or, at least, to control effectively. Its complexity stems from institutional, cultural, economic, and political factors, which interact with each other and reinforce improper practices over time. In this context, the role of public servants is central; officials have a responsibility to safeguard the general interest and manage public resources in accordance with the law. However, they can also become key actors in the reproduction of corrupt behavior, whether due to inadequate incentives, weak control mechanisms, or the absence of effective consequences. Given this duality, it is essential to examine the role of public servants from a comprehensive perspective. This involves analyzing the selection and recruitment processes for officials, the soundness of professional career systems, and the actual application of the principles governing public administration.